Compression for Clinicians : Third Edition. - Venema, Theodore H. (Plural Publishing, Incorporated, 2017)
Explaining the many developments that have taken place in the world of hearing aid compression, fitting methods, and real ear measurement, this text aims to make difficult concepts easier to understand and to explain in plain language many topics pertaining to compression. Directional microphones and digital features of noise reduction, feedback reduction, and expansion are also covered.